AMINO GROUP FORMATION AND GLUTAMATE SYNTHESIS IN STREPTOCOCCUS BOVIS - Burchall, J. J. (1964)
Burchall, J. J. (University of Illinois, Urbana), R. A. Niederman, and M. J. Wolin. Amino group formation and glutamate synthesis in Streptococcus bovis. J. Bacteriol. 88:1038–1044. 1964.—Extracts of Streptococcus bovis grown on NH(4)(+) as a nitrogen source contain a nicotinamide adenine dinucleotide phosphate (NADP)-linked glutamic dehydrogenase and are devoid of alanine dehydrogenase, other amino acid dehydrohygenases, and aspartase. A potential source of reduced nicotinamide adenine dinucleotide phosphate for glutamate synthesis is a NADP and nicotinamide adenine dinucleotide (NAD)-linked glyceraldehyde-3-phosphate dehydrogenase present in the extracts. Experiments with C(14)-labeled glucose and NaHCO(3) indicate that the glutamate carbon skeleton is synthesized by a tricarboxylic acid pathway. The synthesis of the carbon skeleton of glutamate is repressed when glutamate or casein hydrolysate supplement the NH(4)(+)-containing growth medium. Repression of glutamic dehydrogenase and a NAD-linked isocitric dehydrogenase occurs only when complex nitrogen sources, but not when free amino acids, are added to the growth medium.